GAMBARAN BEBERAPA FAKTOR RISIKO GANGGUAN PENDENGARAN PADA PEKERJA DI UNIT PRODUKSI PT. JAKARTA CAKRATUNGGAL STEEL MILLS - Dwi Atin Faidah (Jurnal Ilmiah Medsains, 2022)
The use of work equipment and high technology machines is carried out in the production process to improve the quality and efficiency of production. According to the ILO, there are more than 250 million accidents in the workplace and 160 million workers become sick. The aim of this study was to describe a number of risk factors for workers hearing loss in PT.JCSM production unit. The research model was observasional by using cross sectional design. Population of this research were all workers in production unit. Samples taken by counted 70 respondent. Data collection was conducted by noise measurement using sound level meter and structured interviews with questionnaires. Secondary data was level of hearing loss obtained through a medical cek up by the company. Processing and data analysis were conducted with presentation of frequency distribution in tables. Research showed that age group 46-55 years (46.2%), working period of respondents >10 years (75%), groups of respondents who did not use ear plug (62.5%), groups of respondents who did not use ear muff (75%) occupy the highest proportion has hearing loss. Socialization about the use of PPE which is good especially for ear protectors is still needed to prevent hearing loss in workers.